Association between emergency department length of stay and outcome of patients admitted either to a ward, intensive care or high dependency unit. (5th December 2012) - Flabouris, Arthas; Jeyadoss, Jellsingh; Field, John; Soulsby, Tom
Abstract Objective To evaluate the association of ED length of stay (EDLOS) and outcome of patients admitted to a ward, intensive care (ICU) or stepdown (high dependency) unit (SDU). Methods Design: Retrospective cohort study using linked administrative and clinical data. Setting: 650‐bed, university‐affiliated, tertiary referral hospital, whose ED has approximately 60 000 patient presentations per annum. Participants: Adult patients admitted via the ED, to a ward (ED to ward), ICU (ED to ICU) or SDU (ED to SDU), and whose EDLOS was <24 h. Outcome measures: Hospital outcome and LOS. Results A total of 43 484 patients over 4 years. Median EDLOS was 2:36 h for ICU, 5:07 h for SDU and 7:19 h for ward (P < 0.01) patients. EDLOS differed significantly, based on hospital outcome, for ward (alive, 7:18 h vs died, 7:44 h, P < 0.001), but not SDU or ICU patients. At an EDLOS of 4 and 8 h, 19.4% and 5.2% of ICU, 52.1% and 15.5% of SDU and 77.9% and 32.6% of ward patients remained in the ED. EDLOS was not a significant predictor of death, in comparison with increasing age and admitting unit across all three groups, and higher triage acuity for ED to ward and ED to ICU. Conclusions EDLOS was greater for ED to ward patients, and of the ED to ward patients who died. At an EDLOS of 4 h there were fewer ICU, in comparison with ward, patients remaining in the ED. Future studies that report on EDLOS should differentiate for patients admitted from the ED to the ward, ICU or SDU.